2017
DOI: 10.1002/tox.22399
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of Leucaena leucocephala on the metastasis and invasion of human oral cancer cells

Abstract: Oral cancer is one of the most common cancers worldwide, and metastasis is recognized as a major factor causing its low survival rate. The inhibition of metastasis progress and the improvement of the survival rate for oral cancer are critical research objectives. Leucaena leucocephala from the mimosa branch Leucaena genus is native to Central and South America and has been used as a traditional remedy for treating various disorders. Previous studies have demonstrated antioxidant, anti-inflammatory as well as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…Natural substances, including traditional Chinese medications, greatly contribute to the blockage of tumour metastasis . Rheum palmatum L., a traditional Chinese medication, has been used for the treatment of many diseases such as constipation, jaundice, ulcers, and gastrointestinal hemorrhage .…”
Section: Introductionmentioning
confidence: 99%
“…Natural substances, including traditional Chinese medications, greatly contribute to the blockage of tumour metastasis . Rheum palmatum L., a traditional Chinese medication, has been used for the treatment of many diseases such as constipation, jaundice, ulcers, and gastrointestinal hemorrhage .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported the MAPK signaling pathway as being involved in the regulation of MMP-2 expression in oral cancer [1,8]; thus, we examined the expression of three MAPK pathway-related proteins-ERK1/2, JNK1/2, and p38-using Western blot analysis. The results revealed that PSH reduced the phosphorylation level of ERK2 and p38 to 29% and 33%, respectively, in SCC-9 cells at 40 μM (Fig.…”
Section: Effect Of Psh On the Mapk Pathway In Scc-9 And Sas Cell Linesmentioning
confidence: 99%
“…Metastasis of cancer is a complex molecular mechanism that is often associated with cancer deaths [8]. During metastasis, degradation of the extracellular matrix (ECM) by extracellular proteinases contributes to the progression of tumor cell migration and invasion [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Herbal compositions from natural compounds have been utilized in preclinical or clinical trials with chemopreventive or therapeutic drugs for cancer management . Although chemotherapy and targeted therapy are effective methods for cancer patients, these therapeutic processes have drawbacks of systemic toxicity and drug resistance .…”
Section: Discussionmentioning
confidence: 99%
“…Herbal compositions from natural compounds have been utilized in preclinical or clinical trials with chemopreventive or therapeutic drugs for cancer management. 20,[23][24][25][26][27] Although chemotherapy and targeted therapy are effective methods for cancer patients, these therapeutic processes have drawbacks of systemic toxicity and drug resistance. 28,29 To overcome these problems, studies on combined therapy have focused on identifying phytotherapeutic agents with known action mechanisms that can augment the therapeutic index of chemotherapeutic agents, such as Lentinan combined with oxaliplatin in hepatocellular carcinoma, 30 baicalein combined with docetaxel in thyroid cancer cells, 31 curcumin combined with platinum in ovarian cancer cells, 32 and Astragalus polysaccharides combined with cisplatin in nasopharyngeal carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%